2021
DOI: 10.3389/fcvm.2021.689318
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Promotes Retinal Vascular Endothelial Cell Injury by Inducing CCN1 Expression

Abstract: Purpose: Diabetic retinopathy (DR) is one of the most common diabetic microvascular complications. However, the pathogenesis of DR has not yet been fully elucidated. This study aimed to discover novel and key molecules involved in the pathogenesis of DR, which could potentially be targets for therapeutic DR intervention.Methods: To identify potential genes involved in the pathogenesis of DR, we analyzed the public database of neovascular membranes (NVMs) from patients with proliferative diabetic retinopathy (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…Moreover, CCN1 has been reported to stimulate the production of reactive oxygen species (ROS) through the activation of Rac1 and NADPH oxidase (NOX) 2 [ 27 ]. In line with this, our prior research has demonstrated that CCN1 stimulates ROS production by activating NOX4 in DR [ 21 ]. Considering the well-established critical role of NOX/ROS activation in NETs extrusion [ 33 – 35 ], the aforementioned evidence suggests a potential connection between CCN1 and neutrophils.…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, CCN1 has been reported to stimulate the production of reactive oxygen species (ROS) through the activation of Rac1 and NADPH oxidase (NOX) 2 [ 27 ]. In line with this, our prior research has demonstrated that CCN1 stimulates ROS production by activating NOX4 in DR [ 21 ]. Considering the well-established critical role of NOX/ROS activation in NETs extrusion [ 33 – 35 ], the aforementioned evidence suggests a potential connection between CCN1 and neutrophils.…”
Section: Introductionsupporting
confidence: 70%
“…Moreover, CCN1 has been reported to stimulate the production of reactive oxygen species (ROS) through the activation of Rac1 and NADPH oxidase (NOX) 2 [27]. In line with this, our prior research has demonstrated that CCN1 stimulates ROS production by activating NOX4 in diabetic retinopathy [21]. Considering the well-established critical role of NOX/ROS activation in NETs extrusion [33][34][35], the aforementioned evidence suggests a potential connection between CCN1 and neutrophils.…”
Section: Introductionmentioning
confidence: 53%
“…Focal adhesion signaling pathway was important for maintaining the integrity of retinal vascular structure and function [ 51 , 52 ]. According to the study results, those genes enriched in focal adhesion signaling pathway were considerably upregulated [ 53 – 55 ]. Moreover, proteomic bioinformatic analysis in DR indicated that DR development was closely related to focal adhesion and PI3K-Akt signaling pathway [ 56 ].…”
Section: Discussionmentioning
confidence: 99%